2017
DOI: 10.4172/2157-7595.1000262
|View full text |Cite
|
Sign up to set email alerts
|

Mindful Meditation for Individuals with Asthma and Anxiety: Promising Results from a Multiple Baseline Study

Abstract: Asthma is a disease that affects the overall health and quality of life of millions of children and adults in the U.S. In addition to the physical symptoms and the limitations, many people with asthma also experience anxiety. Psychological interventions used in conjunction with standard treatment have successfully reduced anxiety, as well as improved lung functioning among people with asthma. Mindfulness techniques have been shown to reduce anxiety among children, adolescents and adults. This study sought to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The incidence of myocardial ischemia and death from cardiovascular disease were also reported to be lowered. Cheryl et al (2017) reported that mindfulness meditation led to a moderate improvement in lung functions in a study population composed of patients with asthma. This can be explained by the fact that mindfulness meditation is a stressreduction intervention and stress leads to histamine release which can trigger broncho-constriction and mucus hypersecretion in asthmatics (Yamauchi and Ogasawara, 2019).…”
Section: General Positive Physiological Effects Of Mindfulness Meditamentioning
confidence: 99%
“…The incidence of myocardial ischemia and death from cardiovascular disease were also reported to be lowered. Cheryl et al (2017) reported that mindfulness meditation led to a moderate improvement in lung functions in a study population composed of patients with asthma. This can be explained by the fact that mindfulness meditation is a stressreduction intervention and stress leads to histamine release which can trigger broncho-constriction and mucus hypersecretion in asthmatics (Yamauchi and Ogasawara, 2019).…”
Section: General Positive Physiological Effects Of Mindfulness Meditamentioning
confidence: 99%